Cromatografía de AGV y células somáticas como indicadores de la calidad de leche, bajo dos sistemas de ordeño. Manabí-Ecuador - Calderon Vega, Nadia Evelin (2016)
In this research two milking systems was evaluated: manual and mechanical and its impact on the hygienic quality of milk by measuring two parameters: fatty acid profile, and somatic cells in the milk produced in the province of Manabí, the cantons with higher milk production is analyzed: El Carmen, Flavio Alfaro, Pedernales and Calceta. The samples were analyzed in the laboratory of veterinary diagnostic and food safety “Livexlab” and laboratory analysis of food and water “Labolab”. A completely randomized design was used with factorial arrangement (milking systems for locations) and the Tukey test (P≤ 0.05). Regarding the SCC determined that the samples analyzed were classified as very good for the canton Flavio Alfaro, and range from good to satisfactory for other cantons by the Technical Standards INEN: 9:2012 and that milking type used did not influence the result, not in the chromatographic analysis that the fatty acid content was considerably affected by the type of milking applied. Mostly fatty acids of short, medium and long chain had a greater presence in the milk obtained by manual milking. Research shows that poor management can help milking lipolysis where the fat globule membrane is affected by the different physical changes and mechanical factors.